Economic viability of installing a system of growing hydroponic lettuce - Rover, Suélin; Oliveira, Jorge Luiz Barcelos; Nagaoka, Marilda da Penha Teixeira (Revista de Ciências Agroveterinárias, 2016)
This study aimed to verify the economic viability of a project involving hydroponic lettuce production in Tijucas, Santa Catarina. For data collection, ten interviews were done with the representatives of supermarkets and restaurants located in the metropolitan area of Florianópolis and, based on this information, the volume of sales of that product in those companies was determined. A greenhouse project was developed that could produce enough to meet the identified demand of hydroponic lettuce, which is around 3.840 heads of lettuce/month. The initial investment for the implementation of the project was estimated at R54.352,42, the annual costs of the system are around R33.091,57 and the annual gross revenue is R62.208,00. The economic viability was analyzed using the Net Present Value (NPV), Internal Rate of Return (IRR) and discounted Payback economic indicators. The risk analysis of the investment using the sensitivity analysis was also performed. It was concluded that the project to produce hydroponic lettuce in Tijucas is economically viable, because the the NPV obtained was R156.765,06, the IRR was 53,45% and the recovery time of the investment was 2 years and 2 months.